Analysis of the Implementation of Occupational SafetyPrograms in an Effort to Increase Work Productivity Using a Fault Tree Analysis Approach (Case study: CV. Permata 7, Wonogiri) - Edhi Sulistyoko (IHSA Institute, 2022)
CV. Permata 7 Wonogiri in its operation does not escape the problems faced such as work accidents, occupational diseases and the negative impact of industry on the surrounding environment, the level of human work safety as a production factor is very necessary so that optimal productivity can be achieved. The implementation of work safety programs for workers is an important supporting business in production activities. Every work safety program consists of several program elements and their supporters. In this case the author departs from 2 opinions, namely according to: Edwin B. Flippo and the International Labor Organization (ILO). In this study, the measurement of work safety results and the safe T value, the frequency level for stating the number of accidents that occur every 1,000. 000 hours worked in the current period. Severity level states the number of days lost due to accidents due to accidents for every 1,000,000 working hours of the number of “hours worked” employees. The safety T value is a measurement that aims to compare the results of the accident reduction rate achieved for the work. From the implementation of the occupational health program on CV. Gem 7 Wonogiri can be said to have done quite well. Accidents that occurred in 2005-2007 were 15, 13, 11 times accidents. With the frequency level from 2005-2007 is 64.9; 49.9; 36.1. the severity that occurred in 2005-2007 was 458.9; 284.2; 233.2. With the T-Score of Congratulations in 2006 it was known – 950.2 and in 2007 it was – 1078.2.